Prevention and Management of Elder Abuse - KC, Takma (Journal of Nursing Education of Nepal, 2011)
Elder abuse is violence, neglect, and other harm at elderly persons. The incidence is high among dependent, above 75 years of age and women. Economic burden, emotional stress, dependency and lack of knowledge about elder abuse may contribute to abuse. Physical, psychosocial, sexual, and financial abuses are the major types of abuse. Prevention and management of abuse among elder abuse is important in identifying risk groups. Family members care provider, nurse/health professionals and the community have a major role in identifying, manage and preventing elder abuse.
Keywords: N/A